Prevalence of Hearing Impairment Among High-Risk Newborns in Ibadan, Nigeria - Labaeka, Adeyemi A.; Tongo, Olukemi O.; Ogunbosi, Babatunde O.; Fasunla, James A. (Frontiers in Pediatrics, 2018)
The burden of severe hearing impairment is increasing with two-thirds of these hearing impaired people residing in developing countries. Newborn hearing screening helps to identify early, babies who need intervention in order to prevent future disability. Neither universal nor targeted hearing screening programme is available in Nigeria. OBJECTIVES: This study was carried out to assess the prevalence of hearing impairment among high-risk newborns in UCH and the associated risk factors. MATERIALS AND METHODS: 201 newborns in the neonatal unit of UCH with risk factors for hearing impairment had hearing screening done using automated auditory brainstem response (AABR) at 30, 45 and 70 dB at admission and discharge, and those that failed screening at discharge were rescreened at 6 weeks post-discharge. RESULTS: 83 (41.3%) and 32 (15.9%) high-risk newborns failed at admission and discharge screening respectively, and 19 (9.5%) still failed at follow up screening. The majority of hearing loss at follow up was bilateral (94.7%) and severe (52.6%). The risk factors associated with persistent hearing loss at follow up were acute bilirubin encephalopathy (RR = 11.2, CI: 1.4 – 90.6), IVH (RR= 8.8, CI: 1.1 – 71.8), meningitis (RR = 4.8, CI: 1.01 – 29), recurrent apnoea (RR= 2.7, CI: 1.01 – 7.3), severe perinatal asphyxia NNE III (RR = 7, CI: 2.4 – 20.2). CONCLUSION: Severe and bilateral hearing impairment is a common complication among high risk newborns in UCH persisting till 6 weeks post-neonatal care. Severe perinatal asphyxia with NNE III, ABE, IVH, meningitis and administration of amikacin for more than 5 days were significant risk factors. We recommend that SCBU graduates with these risk factors should have mandatory audiologic evaluation at discharge.